Pendampingan Pemanfaatan Stiker Viral untuk Membuat Komik Guna Meningkatkan Literasi Produktif Siswa Sekolah Dasar - Purnanto, Arif Wiyat; Pratama, Febrian Arif; Fitria, Savira Ananda; Andini, Puput; Hurairah, Muhammad (Jurnal Abdimas Komunikasi dan Bahasa, 2023)
Sidorejo 1 Elementary School was the only elementary school in Surakan Hamlet, Sidorejo Village, Tegalrejo District, Magelang Regency. This school had become one of the community's mainstay schools because of its strategic location and easy accessibility. Despite having garnered high trust from the community, this school faced several obstacles. One of the main problems was related to facilities and infrastructure. Based on data obtained from the website Sekolah.data.kemdikbud.go.id, many of the facilities and infrastructure at SD Negeri Sidorejo 1 were in poor condition. Of the six classrooms, 3 classrooms were slightly damaged, 2 classrooms were moderately damaged, and 1 classroom was heavily damaged. Other facilities also experienced similar issues. The library suffered moderate damage, the science laboratory suffered heavy damage, and the sanitation facilities for teachers and students suffered light and severe damage. The aim of the service was to overcome student literacy problems at SD Negeri Sidorejo 1 Tegalrejo, Magelang district. The focus of literacy that was targeted for improvement was productive literacy. The method used was Participatory Rural Appraisal involving teachers and students at the school. The results showed that teachers had been socialized regarding productive literacy. Meanwhile, students had successfully completed a comic creation project using viral stickers. It was hoped that in the future, students could further develop the use of viral stickers to produce other productive literacies. Tujuan pengabdian ini adalah untuk mengatasi problem literasi siswa di SD Negeri Sidorejo 1 Tegalrejo kabupaten Magelang. Fokus literasi yang ingin ditingkatkan yaitu literasi produktif. Metode yang  digunakan  adalah Participatory  Rural Appraisal dengan melibatkan guru dan siswa di sekolah tersebut. Hasilnya menunjukkan bahwa guru telah tersosialisasi terkait literasi produktif. Sedangkan siswa sudah sudah berhasil menyelesaikan proyek penyusunan komik dengan memanfaatkan stiker viral. Harapan kedepan siswa dapat lebih mengembangkan pemanfaan stiker viral untuk menghasilkan literasi-literasi produktif lainnya.